INTERNALISASI NILAI-NILAI ASMAUL HUSNA DALAM PENDIDIKAN AGAMA ISLAM UNTUK MEMBENTUK KARAKTER SISWA SEKOLAH DASAR - Ulfiyah Riska Damayanti; M Mahbubi (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2025)
This study aims to examine the process of internalizing Asmaul Husna values in Islamic Religious Education (PAI) learning as a strategy for character development among students at Madrasah Ibtidaiyah (MI) Nurun Najah, Buleleng Regency, Bali. The background of this research stems from a moral crisis among elementary school students, characterized by declining empathy, discipline, and social responsibility. The study employs a qualitative approach with a case study design, involving the school principal, Islamic education teachers, students, and parents as informants. Data were collected through interviews, observations, and documentation. The findings reveal that the internalization of Asmaul Husna is carried out through daily routines, teacher role-modeling, and religious activities such as congregational prayer and almsgiving. Values such as Ar-Rahman (the Most Merciful), Al-Adl (the Just), and Al-Ghaffar (the Forgiving) are not only understood but are also reflected in students’ daily behavior, including helping others, forgiving, and showing empathy. In addition, parents observed positive changes in their children's attitudes at home. This study affirms that a religious, contextual, and applicable approach in Islamic Religious Education effectively shapes students’ character to be religious, honest, disciplined, and responsible. The internalization of Asmaul Husna has proven to be an effective strategy for instilling moral and spiritual values from an early age.